(untitled) (Experimental biology, 2009)
For cell selection carrying out complex fungus phytotoxin Septoria nodorum was used ( Ph-1,Ph-2,Ph-3,Ph-5) which was put in explant culture with the concentration 0.01-0.05%. Gross intensity while comparing two investigated genotypes isn’t differed that is response reaction to the stress is approximately the same. Given experimental investigations tasks include: optimization of fungus cultivation conditions, biomass making for cultural filtrate preparation (KF),toxin identification in KF and in mycelium extracts.